Efektivitas Pelatihan Kader Posyandu dalam Pengisian Buku KMS di Posyandu Remaja Klaten - Nur Hidayah; Tria Puspita Sari; Annisa Cesaaria (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
Background:One of the duties of Posyandu cadres in Posyandu activities is to keep records. Conditions in the field are that there are still many posyandu cadres who do not know how to fill in the KMS book. So far, the cadres have received training on the MCH Handbook. The approach used is conventional. Purpose:This study aims to determine the effectiveness of training for youth posyandu cadres in completing the MCH handbook. Methode: This type of research is pre-experimental, with a one-group pre-test-post-test group design. The population in this study were all posyandu cadres in Lemahireng Pedan Klaten Village, consisting of 10 people. Sampling technique with total sampling. Result: Data analysis using the Wilcoxon Signed Ranks Test, obtained P = 0.006 (p <0.05) so that there is a significant difference in the knowledge of cadres before and after being given training in filling out the Health Card book (KMS). Keywords: Training, Cadre, KMS Book